Human rights: the critical view of the Brazilian population in the two decades after the military governments (Research, Society and Development, 2021)
The main objective of this work is to analyse the meaning and importance of human rights in Brazil when seen from the perspective of the population regarding themes such as freedom of belief and the performance of police forces. The issue of human rights in contemporary Brazilian history is therefore approached, contextualizing it in the Brazilian political scenario at that time. This qualitative research adopts bibliographic review and collection of documentary information, gathering data sought in the space reserved for readers of a popular Brazilian magazine between the 1980s and the 2000s. The period chosen was between 1985 and 2004, that is to say, exactly two decades after the end of the period marked by the Brazilian civil-military dictatorship, which took place from 1964 to 1985, period in which the human rights theme had great repercussion in Brazil, for political reasons. This research makes use of content analysis and uses categorization in order to review the opinions expressed by readers. It is inferred that the readers' freedom of expression was also used as a way of amplifying voices and ideas on the subjects delimited here. It could also be seen that the Catholic majority gave way to religious plurality in the period portrayed and that criticism of police violence extended throughout the analysed period, culminating in restructuring and implementation of public policies to improve police forces.